Yamuna Purple-10 (G-404): A new promising garlic variety - Dubey, B K; Gupta, P K (Indian Horticulture, 2021)
The new variety of garlic Yamuna Purple-10 was tested at different locations and found superior at Jammu, Karnal, Kalyanpur, Chiplima, Jabalpur, Durgapura, Akola, Junagarh, Rajgurunagar, Coimbatore and Dharwad. It has also been identified for cultivation at National level and accordingly notified by the Government of India vide notification No. SO 4272 (E) dated 26 Nov. 2019 and recommended for cultivation in Zone-II (Jammu, Ludhiana, Delhi, Haryana and Rajasthan) and Zone-IV (Madhya Pradesh, Chhattisgarh, Karnataka, Maharashtra). It is recommended for planting by the second fortnight of October and becomes ready for harvesting in about 165-175 days. Average bulb yield is 18-20 tonne per hectare.